STRATEGI PEMBELAJARAN MELALUI JAMBI FUN BOOK: PENDEKATAN KONTEKSTUAL KREATIF UNTUK MENINGKATKAN LITERASI DI JAMBI - Wati, Sarmila; Sophia Rahmawati (LPPM STAI Muhammadiyah Probolinggo, 2025)
Low literacy interest in Jambi Province poses a significant educational challenge. This community service program aims to enhance reading interest and literacy skills through Jambi Fun Book, a creative medium rooted in local cultural wisdom. Developed by the Jambi Fun Book literacy community, the program employs active participatory observation and descriptive qualitative methods, involving training, mentoring, discussions, and practice. Target participants include elementary school students, youth, teachers, and literacy volunteers. Expected outcomes are the development of creative local culture-based teaching materials, improved volunteer skills, increased community participation in literacy activities, and enhanced learning media. Findings indicate that using culturally-based teaching materials effectively increases reading interest, fosters active engagement, and strengthens the connection between reading content and daily life.